2018
DOI: 10.1007/s13205-018-1193-3
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable and green process for scouring of cotton fabrics using xylano-pectinolytic synergism: switching from noxious chemicals to eco-friendly catalysts

Abstract: The objective of this research was to develop an appropriate, eco-friendly, cost-effective bioscouring methodology for removing natural impurities from cotton fabric. Maximum bioscouring was achieved using 5.0 IU xylanase and 4.0 IU pectinase with material to liquid ratio of 1:15 in a 50 mM buffer (glycine-NaOH buffer, 1.0 mM EDTA and 1% Tween-80, pH 8.5) with a treatment time of 60 min at 50 °C and an agitation speed of 60 rpm. The bioscoured cotton fabrics showed a gain of 1.17% in whiteness, 3.23% in bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The bioscouring was performed with 5.0 IU xylanase and 4.0 IU pectinase from Bacillus pumilus strain AJK (MTCC 10414) along with surfactants such as 1.0 mM EDTA and 1% Tween-80 at high pH 8.5 for 1 h at 50 °C. They observed improvement in whiteness, brightness, and reduction in yellowness by 1.2%, 3.2%, and 4.2% respectively that is better in comparison to chemical-based alkaline scouring method (Singh et al 2018). El et al (2018) reported improvement in desizing, bioscouring and bio-finishing efficiency using xylanase obtained from T. longibrachiatum KT693225 without any requirement of additives.…”
Section: Xylanase Employed In Textile Industriesmentioning
confidence: 99%
“…The bioscouring was performed with 5.0 IU xylanase and 4.0 IU pectinase from Bacillus pumilus strain AJK (MTCC 10414) along with surfactants such as 1.0 mM EDTA and 1% Tween-80 at high pH 8.5 for 1 h at 50 °C. They observed improvement in whiteness, brightness, and reduction in yellowness by 1.2%, 3.2%, and 4.2% respectively that is better in comparison to chemical-based alkaline scouring method (Singh et al 2018). El et al (2018) reported improvement in desizing, bioscouring and bio-finishing efficiency using xylanase obtained from T. longibrachiatum KT693225 without any requirement of additives.…”
Section: Xylanase Employed In Textile Industriesmentioning
confidence: 99%
“…Enzyme activity of Bioprep ® 3000 L was studied firstly with the soluble substrate of polygalacturonic acid, so the enzyme-catalyzed reaction occurred under homogenous conditions (see item 3.1), while the cotton fabric used in bioscouring is insoluble, the reaction heterogenous and the enzyme must function at solid/liquid interfaces. Here, surfactants lower the surface tension of the aqueous scouring bath, which ultimately improved the penetration of the enzymes into the fibers (AGRAWAL et al, 2008;SINGH et al, 2018). Surfactants can also have a stimulatory effect by improving the turnover number of pectinase and increasing the contact frequency between the active site of the enzyme and the cotton substrate (OUMER; ABATE, 2017) as well as aiding in adsorption and desorption of the enzyme to and from the fabric.…”
Section: Enzymatic Scouring Of Cotton Using Pectate Lyasementioning
confidence: 99%
“…These multiple forms may have different biochemical properties, specific activity, yield, and efficiency of xylan hydrolysis . Interest in the use of xylanases has increased during recent 5–10 years due to their eco‐friendly applicability in various industries such as animal feed, biobleaching of paper pulp, bioscouring of textile fibres, production of xylo‐oligosaccharides, waste‐water treatment, extraction and clarification of fruit juices, deinking of waste paper, baking industry, oil extraction, and still new applications are coming up especially for biofuel production.…”
Section: Introductionmentioning
confidence: 99%